Stereotactic MRI-guided radiation therapy for localized prostate cancer (SMILE): a prospective, multicentric phase-II-trial - Ristau, Jonas; Hörner-Rieber, Juliane; Buchele, Carolin; Klüter, Sebastian; Jäkel, Cornelia; Baumann, Lukas; Andratschke, N.; Garcia Schüler, H.; Guckenberger, M.; Li, M.; Niyazi, M.; Belka, C.; et al. (Radiation oncology, 2022)
Normofractionated radiation regimes for definitive prostate cancer treatment usually extend over 7-8 weeks. Recently, moderate hypofractionation with doses per fraction between 2.2 and 4 Gy has been shown to be safe and feasible with oncologic non-inferiority compared to normofractionation. Radiobiologic considerations lead to the assumption that prostate cancer might benefit in particular from hypofractionation in terms of tumor control and toxicity. First data related to ultrahypofractionation demonstrate that the overall treatment time can be reduced to 5-7 fractions with single doses > 6 Gy safely, even with simultaneous focal boosting of macroscopic tumor(s). With MR-guided linear accelerators (MR-linacs) entering clinical routine, invasive fiducial implantations become unnecessary. The aim of the multicentric SMILE study is to evaluate the use of MRI-guided stereotactic radiotherapy for localized prostate cancer in 5 fractions regarding safety and feasibility.
Gesehen am 05.09.2022